Representações de saúde e trabalho na perspectiva de servidores administrativos de uma prefeitura mineira - Borges, Andréa Gonçalves (2022)
Introduction: The intense transformations in the world of work have exposed new management mechanisms, which may represent an increase in health risks for the worker. In the field of meanings of the health-disease process, work is central to the understanding of expectations and the worker's attitude towards life and work itself. Objective: To understand the relation between health representations and work-related factors that impact on the health-disease process of an administrative team in a City Hall in Triângulo Mineiro, from the perspective of the workers themselves. Method: An integrative literature review was carried out in order to collect scientific productions that enabled the understanding of the knowledge boundary on the subject. This was followed by a field research, in which a qualitative methodology was adopted; composed of a questionnaire, for sociodemographic characterization, and audio-recorded semi-structured interview, mediated by the Semi-structured Elicitation Test technique, both obtained in a virtual environment, meeting biosecurity protocols, due to the Covid-19 pandemic. Twenty-six public servants, occupying the position of Administrative Officer, participated. The interviews were transcribed in full and submitted to content analysis in the thematic modality, under the contribution of the Theory of Social Representations and Workers' Health. Research findings: The results enabled the identification of 4 categories: The social representation of health as absence of suffering; The valorization of the dimensions of social, physical and mental health in the work environment; A request: humanization at work; The organization of work has repercussions on the health-disease process of administrative employees. The multidimensional nature of the phenomena associated with workers' health emerged, highlighting the experience of social support as a health promoter in the work environment. On the other hand, singularities that have a negative impact on the workers’ health were made explicit, such as ergonomic problems, lack of technological resources and the deficiency of communication between managers and the work team, conceived as an absence of recognition and disrespect for the needs and limitations of employees. A set of individual accountability was evidenced, derived from the historical, social and economic appropriation of the concept of health. This discourse corroborates the one embodied in the neoliberal conjuncture, which weakens the spaces for collective discussion and effective changes in the structural reality of work contexts. Conclusion: Studies on the health of public servants in administrative positions reveal the need for new strategies in academic production and in care practices in face of the historical fragility of policies aimed at workers' health in the public service. The scientific contributions of the study point to the reproduction of practices naturalized in the work environment regarding the meaning of the value of health and medical care. As for practical contributions, it is proposed to establish shared spaces for planning work activities, in order to ensure the discussion about the origin of the current model of work organization and about the ways to humanize relationships.